2019
DOI: 10.3390/ijms20215321
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Proteins: Dynamic Biomolecules to Counter Plant Biotic and Abiotic Stresses

Abstract: Due to the present scenario of climate change, plants have to evolve strategies to survive and perform under a plethora of biotic and abiotic stresses, which restrict plant productivity. Maintenance of plant protein functional conformation and preventing non-native proteins from aggregation, which leads to metabolic disruption, are of prime importance. Plant heat shock proteins (HSPs), as chaperones, play a pivotal role in conferring biotic and abiotic stress tolerance. Moreover, HSP also enhances membrane sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
187
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 341 publications
(195 citation statements)
references
References 256 publications
(297 reference statements)
8
187
0
Order By: Relevance
“…Assuming that the ‘Barnea’ cultivar is more tolerant to heat stress compared to the ‘Souri’ cultivar in regard to fruit development and oil accumulation [ 36 ], suggests that induction of heat-shock proteins may contribute to the olive plant’s tolerance to heat stress. This assumption is in agreement with other studies which found that heat-shock proteins are involved in heat tolerance [ 26 , 47 , 48 ]. Analysis of OeHSP70 expression also showed the same pattern, in which the differences between the expression levels in the HT and the MT environments were much higher in the ‘Barnea’ cultivar than in the ‘Souri’.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Assuming that the ‘Barnea’ cultivar is more tolerant to heat stress compared to the ‘Souri’ cultivar in regard to fruit development and oil accumulation [ 36 ], suggests that induction of heat-shock proteins may contribute to the olive plant’s tolerance to heat stress. This assumption is in agreement with other studies which found that heat-shock proteins are involved in heat tolerance [ 26 , 47 , 48 ]. Analysis of OeHSP70 expression also showed the same pattern, in which the differences between the expression levels in the HT and the MT environments were much higher in the ‘Barnea’ cultivar than in the ‘Souri’.…”
Section: Discussionsupporting
confidence: 93%
“…Heat-shock proteins positively regulate antioxidant enzymes which detoxify reactive oxygen species. They also enhance plant immunity by the accumulation and stability of pathogenesis-related proteins produced under biotic stresses [ 26 ]. During the onset of stress, plants reduce normal protein production, and transcribe and translate heat-shock proteins.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations